2012
DOI: 10.1111/j.1468-1331.2012.03693.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced urinary glutamate levels are associated with the frequency of migraine attacks in females

Abstract: We show here that female migraineurs exhibit decreased urinary glutamate levels which are associated with a 4.04-fold higher risk for migraine and correlated with patients' frequency of migraine attacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Elevated urinary glutamic acid levels have been associated with a 4-fold higher risk for migraines in females. 74 Beyond their clinical relevance, the three selected reactions are catalyzed by enzymes with well-known properties, and use a simple, oxygen-dependent reaction that produces H 2 O 2 . 75 The H 2 O 2 is then utilized to oxidize a chromogenic agent in a secondary reaction catalyzed with HRP.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated urinary glutamic acid levels have been associated with a 4-fold higher risk for migraines in females. 74 Beyond their clinical relevance, the three selected reactions are catalyzed by enzymes with well-known properties, and use a simple, oxygen-dependent reaction that produces H 2 O 2 . 75 The H 2 O 2 is then utilized to oxidize a chromogenic agent in a secondary reaction catalyzed with HRP.…”
Section: Resultsmentioning
confidence: 99%
“…The association between the dysregulation of glutamate and migraine attacks is widely described in the literature. Previous studies have observed that migraine patients present higher glutamate levels than controls in plasma, platelets, saliva or cerebrospinal fluid (CSF) (3,1825), and this effect seems to be reflected in a reduction of urinary glutamate levels (26). It has been reported that in pathologic conditions associated with a large increase of glutamate in brain tissue (which has been shown to occur in pathologies such as ischemia, epilepsy, and presumably migraine), there is a diffusion of glutamate from the extracellular space to the blood following a gradient of concentration, which could explain the increase of systemic glutamate levels observed in these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances in several amino metabolites have been previously associated with CSD both in brain tissue (Jones et al 2012 ; Cavus et al 2008 ; Levy and Degnan 2013 ; Fabricius et al 1993 ) and body fluids (Ragginer et al 2012 ; de Tommaso et al 2012 ). Our MSI experiments revealed a significant increase in several amino metabolites in the cortex after CSD, notably GABA, an inhibitory neurotransmitter that counters the excitatory glutamate released by CSD.…”
Section: Resultsmentioning
confidence: 99%